Evaluation of Thermal Evolution Profiles and Estimation of Kinetic Parameters for Pyrolysis of Coal/Corn Stover Blends Using Thermogravimetric Analysis. (19th March 2014) - Bhagavatula, Abhijit; Huffman, Gerald; Shah, Naresh; Honaker, Rick
Abstract : The thermal evolution profiles and kinetic parameters for the pyrolysis of two Montana coals (DECS-38 subbituminous coal and DECS-25 lignite coal), one biomass sample (corn stover), and their blends (10%, 20%, and 30% by weight of corn stover) have been investigated at a heating rate of 5°C/min in an inert nitrogen atmosphere, using thermogravimetric analysis. The thermal evolution profiles of subbituminous coal and lignite coal display only one major peak over a wide temperature distribution, ~152–814°C and ~175–818°C, respectively, whereas the thermal decomposition profile for corn stover falls in a much narrower band than that of the coals, ~226–608°C. The nonlinearity in the evolution of volatile matter with increasing percentage of corn stover in the blends verifies the possibility of synergistic behavior in the blends with subbituminous coal where deviations from the predicted yield ranging between 2% and 7% were observed whereas very little deviations (1%–3%) from predicted yield were observed in blends with lignite indicating no significant interactions with corn stover. In addition, a single first-order reaction model using the Coats-Redfern approximation was utilized to predict the kinetic parameters of the pyrolysis reaction. The kinetic analysis indicated that each thermal evolution profile may be represented as a single first-order reaction. Three temperature regimes were identified for each of the coals while corn stover and the blends were analyzed using two and four temperature regimes, respectively.